Optimal Control Model Pemanenan Prey-Predator di Area Konservasi Ikan - Yunita Nur Afifah; MNH Qomarudin; Imamatul Ummah (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2020)
The longer the fish population will decrease or experience extinction due to continuous fishing by humans. Conservation areas are needed as an effort to maintain the marine ecosystem and avoid extinction. The dynamics stability of the model can be seen from the equilibrium point. So that the application of mathematics can be used to make prey-predator population dynamics models and determine ways to optimize fish harvesting. The mathematical model is divided into three populations and in two different areas. To get maximum harvesting (E), use the Pontryagin Maximum Principle. So that the maximum benefit obtained when harvesting is 0.77 to 0.95.